DNA computing and molecular programming : 20th International Conference, DNA 20, Kyoto, Japan, September 22-26, 2014. Proceedings - Kobayashi, Satoshi; Murata, Satoshi (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 20th International Conference on DNA Computing and Molecular Programming, DNA 20, held in Kyoto, Japan, in September 2014. The 10 full papers presented were carefully selected from 55 submissions. The papers are organized in many disciplines (including mathematics, computer science, physics, chemistry, material science and biology) to address the analysis, design, and synthesis of information-based molecular systems.